2020
DOI: 10.3389/fpsyg.2020.01072
|View full text |Cite
|
Sign up to set email alerts
|

The Systematic Impact of Personal Characteristics on Entrepreneurial Intentions of Engineering Students

Abstract: The impact of personal characteristics on entrepreneurial intention is a classic topic in the field of entrepreneurship research. Previous research mostly used simple linear models, leading to a gap in the study on the interrelationship among personal characteristics and their systematic influence on entrepreneurial intention. This study investigates the interrelationship among the four specific entrepreneurial characteristics (i.e., need for achievement, locus of control, risk-taking propensity, and creativit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 93 publications
3
27
0
2
Order By: Relevance
“…Differently, the desire to take risks is the primary key in growing a business. In their analysis, Ozaralli and Rivenburgh (2016) also found that there is a significant relationship between the tendency to risk-take on Entrepreneurial Intention, the same thing as this study found in the Sun et al (2020) study that there is no influence on Entrepreneurial Intention and significant risk-taking. The same thing between Locus of control and Entrepreneurial Intention.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Differently, the desire to take risks is the primary key in growing a business. In their analysis, Ozaralli and Rivenburgh (2016) also found that there is a significant relationship between the tendency to risk-take on Entrepreneurial Intention, the same thing as this study found in the Sun et al (2020) study that there is no influence on Entrepreneurial Intention and significant risk-taking. The same thing between Locus of control and Entrepreneurial Intention.…”
Section: Discussionsupporting
confidence: 64%
“…The need for achievement has an important and positive impact on entrepreneurial intent (Untu and Widjaja, 2019). However, there is no impact of Need For Achievement with Entrepreneurial Purpose in the study by Sun et al (2020) reports. Dohse and Walter (2012) have determined that one of the variables affecting the desire of a person to become an entrepreneur is the need for achievement.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Previous research mostly applied simple linear models, which led to a gap in the mutual relations between personal traits and their systematic influence on entrepreneurial intentions. Sun et al [14] examined the mutual relation between four specific entrepreneurial characteristics (i.e. need for achievement, locus of control, risk taking tendency and creativity) and their systematic influence on the entrepreneurial intentions of students of technical fields.…”
Section: Locus Of Controlmentioning
confidence: 99%